RECOMMENDATION SYSTEM FOR THE TRAVEL INDUSTRY - KONDRA, ARTUR; LOIKO, NAZARII; PASICHNYK, SERHII; KUNANETS, NATALIIA; MASHIKA, HANNA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Various factors cause the need for tourism in modern society and reflects the complex aspects of modern life. Modern society highly values cultural exchange. Tourism provides people with the opportunity to explore new cultures, traditions, languages and customs, promoting understanding and mutual respect between different nationalities. The growing level of stress and tension in modern life creates a need for rest and relaxation. Tourism allows people to break away from everyday routines, immerse themselves in nature or enjoy cultural travel. Tourism is becoming an important segment of the global economy, providing jobs, fostering the development of local industries, and stimulating investment in infrastructure. Traveling opens up new opportunities for education and self-improvement. People gain new knowledge, develop their worldview and broaden their horizons through interaction with other cultures. Tourism can promote social integration, especially for less developed regions. Interaction between tourists and locals fosters mutual understanding and the development of socio-cultural relations. Growing environmental awareness is leading to the popularity of environmentally friendly forms of tourism, such as ecotourism and travel to nature reserves, contributing to environmental conservation. Tourism can help countries, regions or cities create a positive image, attracting attention and increasing their attractiveness to tourists and investors. The combination of these factors defines and drives the need for tourism in modern society, making it an important aspect of human life and international relations. In Ukraine, tourism is recognized as one of the industries that require priority development and requires the use of information technologies and systems. The purpose of this paper is to analyze the processes of creating an information system for the tourism industry. The object of research is the process of creating a recommendation system. The subject of the study is the methods and means of developing a recommendation system.